Peran Pemerintah dalam Meningkatkan Kesadaran Masyarakat Tentang Kebersihan Lingkungan di Kelurahan Tounsaru Kecamatan Tondano Selatan - Runturambi, Princess Chevania; Pangalila, Theodorus; Biringan, Julien (Tumoutou Social Science Journal, 2026)
This study aims to determine the government's role in increasing public awareness of environmental cleanliness in Tounsaru Village, South Tondano District. The research method used is descriptive research with a qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis techniques used data reduction, data presentation, and conclusion drawing. The results show that the village government has carried out its role through socialization, appeals, and routine community service programs such as Clean Friday. These efforts have had a positive impact on increasing public awareness. However, there are still obstacles such as limited cleanliness facilities and infrastructure and unequal community participation. Therefore, it is necessary to improve facilities and strengthen regulations to support the creation of a clean and healthy environment.